OCEANIC SEDIMENTATION SETTINGS AND FAUNA ASSOCIATIONS IN THE PALEOZOIC ON THE SOUTHERN FRAMING OF THE WEST SIBERIAN PLATE - Sennikov N.V.; Iwata K.; Ermikov V.D.; Obut O.T.; Khlebnikova T.V. (My University, 2003)
The geologic structure, geochemistry, lithology, and paleontology of the Late Cambrian-Early Ordovician volcanosedimentary Zasur'ya Group in Gorny Altai are considered. Its geochemical parameters, lithologic features, and biomarkers are indicative of its oceanic genesis. The regularities of the spatial distribution of various facies types of Zasur'ya Group sections are revealed. Eight conodont zones are recognized there. They allow precise dating of the unit. The Gorny Altai sector of the Paleo-Asian ocean has been proven to exist for ca. 40 Ma. The stratigraphic position of the metamorphic and volcanosedimentary deposits of Rudny Altai is considered. In the Chara sector of the Paleo-Asian ocean, the age position of the volcanosedimentary units is refined and the stratigraphic levels of oceanic sediments are outlined.
Keywords: PALEO-ASIAN OCEAN; MIDDLE DEVONIAN KARAKOITAS FORMATION; CONODONTS; RADIOLARIANS; GORNY ALTAI; RUDNY ALTAI; Палеоазиатский океан; среднедевонская каракойтасская и нижнекарбоновая верачарская свиты; конодонты; радиолярии; горный Алтай; Рудный Алтай; Ordovician; Cambrian; 551.73+56(113)/571.15; Paleozoic::Ordovician; Paleozoic::Cambrian; Палеозой::Кембрийская; Палеозой::Ордовикская